Workshop digital marketing dan video kreatif Karang Taruna Pendowoharjo untuk membangun citra positif digital media - Daffa Maulana Hidayat; Popi Andiyansari; Akhmad Afnan (Nur Science Institute, 2026)
This community service activity aims to enhance the knowledge, skills, and self-confidence of the youth of Karang Taruna Pendowoharjo, considering that the utilization of social media has not yet been optimized for productive digital engagement. The program was conducted through a Digital Marketing and Creative Video Design Workshop. The background of this activity is the important role of youth as agents of change in supporting digital-based village development, as well as the limited capacity of youth organizations to manage digital content effectively. The implementation methods included lectures, discussions, demonstrations, and hands-on practice in creating visual and creative video content using Canva and CapCut applications. The evaluation was conducted through pre- and post-tests to measure participants' improvement in understanding. The results indicated a significant increase in participants' comprehension of digital marketing concepts, the use of social media as a branding tool, and technical skills in creating digital content. The pre-test results, which were initially 80%, increased to 86% in the post-test. In addition, the activity increased participants' self-confidence and active participation during the learning process. Therefore, the workshop proved effective in supporting youth empowerment in the village and in building a positive image of Karang Taruna through the sustainable use of digital media.